If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying M + -2(1 + -3m) = 6 + 3(4 + -1m) M + (1 * -2 + -3m * -2) = 6 + 3(4 + -1m) M + (-2 + 6m) = 6 + 3(4 + -1m) Reorder the terms: -2 + M + 6m = 6 + 3(4 + -1m) -2 + M + 6m = 6 + (4 * 3 + -1m * 3) -2 + M + 6m = 6 + (12 + -3m) Combine like terms: 6 + 12 = 18 -2 + M + 6m = 18 + -3m Solving -2 + M + 6m = 18 + -3m Solving for variable 'M'. Move all terms containing M to the left, all other terms to the right. Add '2' to each side of the equation. -2 + M + 2 + 6m = 18 + 2 + -3m Reorder the terms: -2 + 2 + M + 6m = 18 + 2 + -3m Combine like terms: -2 + 2 = 0 0 + M + 6m = 18 + 2 + -3m M + 6m = 18 + 2 + -3m Combine like terms: 18 + 2 = 20 M + 6m = 20 + -3m Add '-6m' to each side of the equation. M + 6m + -6m = 20 + -3m + -6m Combine like terms: 6m + -6m = 0 M + 0 = 20 + -3m + -6m M = 20 + -3m + -6m Combine like terms: -3m + -6m = -9m M = 20 + -9m Simplifying M = 20 + -9m
| 5x+14=16-10x | | 0.25(2x+1)-1/x-1=x/2 | | 4(x+1)2-2(2x-5)(x+2)=0 | | 15u^2+u-2=0 | | (x+3)-(2x-7)+6=13(x-1)+4(2x+1)-7x | | x+5/3-18-2x/4=x+3/6 | | (2k+5/4)=2-(k+2/3) | | (7k/4)=2-(2k/3) | | (4x+1)(3x+6)= | | 1/5x+1/11(x+14) | | 3x-2Y=150 | | 2.9x=27.55 | | 4.8x=40.8 | | 24x^3+36x^2= | | 3X=2Y+150 | | 2x+12=12-10x | | x(-15x-64)-33=0 | | -9-6x=5x+14 | | (x+3/3)-(x-1/2)=4 | | 5y^2-4y-30=0 | | y^2-x^2-12y-8x-16=0 | | 16(x+1)-2(3-x)=-3(x+6) | | x+3+3(x+2)=9-2x | | 10x+4(-3x+1)-1=2x-(4x+1) | | 5+6(x+3)=4(x-1)+7 | | 4,6+z=5,6-3z | | 0,2x+2,5=1,5x-10,5 | | -y+2=-2y+0,5 | | 1,5p-2,3=-2,3+4p | | x^2dy-y^2dx=0 | | 9p+79= | | 2x-4=9x-28 |